Substantive justice of e-faktur as electronic evidence in tax crimes - Prasetyo, Erwan B. (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study analyzed legal uncertainty in the use of e-Faktur as electronic evidence in tax crimes, especially related to weak normative regulations and the absence of standard digital evidentiary standards in the Indonesian criminal justice system. The main problem studied was the lack of explicit recognition of electronic documents, including e-Faktur, as stand-alone evidence in the Criminal Code, and the absence of a distinguishing mechanism between technical administrative errors and deliberate criminal violations. This study used a normative juridical approach with an analysis of national laws and regulations, legal doctrine, and case studies, and is combined with a comparative approach through a comparison of e-Faktur proving practices in Italy, Peru, Rwanda, and the Peppol system. The results of the study found that positive legal regulations in Indonesia are not adaptive to the complexity of digital proof, thus creating a risk of criminalization of taxpayers who commit technical errors without malicious intent. The findings also showed that there are no technical guidelines for forensic examination of e-Faktur that are in accordance with international standards, as well as the lack of discretion of judges in considering aspects of substantive justice in digital taxation cases. The implications of this study emphasize the importance of revising the Criminal Code to include electronic evidence as legal evidence, the preparation of special regulations regarding electronic evidence in tax cases, and the development of technical guidelines for law enforcement officials related to digital forensics and the principle of prudence in handling cases. The novelty aspect of this study lies in the integration of substantive justice perspectives and transcendental approaches in the proof of digital law, as well as the use of international comparative models that have not been widely adopted in previous studies. The final conclusion of this study is that proving e-Faktur requires a legal reformulation that is more accommodating to technological developments and human values, in order to realize a fair, proportional, and substantive digital criminal justice system.